(3GdebGeGJ GdLhRjI aj GdeYGfj GdhYXjI hTQM GdcdeGJ GddZhjIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf GddZI GdYQHjI CQJH bOe aj GdCOhGJ s
(3BNQgG (B:s
(3hfMf fSCd hGgH Gdaghe, Cf jfaYfG HLejY GdYdhe, Efg hdj Pdc hGdbGOQ Ydjg HQMeJg s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGX s
(3hCcedJ Hbde BNQ HOAkG ef GdebGeI GdNGeSI hGdKdGKjs
(3f hHChdgG eWGdYGJ hJedjcGJ CbOegG eWGdYI deMeO Hf CMeO GdfSQj aj SfI (B792(3g``````s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B535 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B77 s
Keywords: (3GdCOHs